2000
DOI: 10.1164/ajrccm.162.2.9908024
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-Thrust Ventilation in Hypercapnic Patients with Acute Respiratory Distress Syndrome

Abstract: Techniques of tracheal gas insufflation (TGI) have been shown to enhance CO(2) clearance efficiency in mechanically ventilated patients with acute respiratory distress syndrome (ARDS). Clinical studies have explored the effects of such techniques only at moderate intratracheal gas flow rates, with TGI superimposed to mechanical ventilation in a continuous fashion, or synchronized to the expiratory phase of the duty cycle. We examined the effects of intratracheal pulmonary ventilation (ITPV), delivering the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Prone positioning has demonstrated improvement in hypoxia at the expense of increasing ICP and decreasing CPP (6,114). Tracheal gas insufflation may allow low tidal volumes with concomitant treatment of hypercarbia or maintenance of normocarbia (87,119). Extracorporeal membrane oxygenation has been used with success in trauma patients with ARDS, particularly demonstrating improved mortality when initiated early (18).…”
Section: Ventilator Management After Tbimentioning
confidence: 99%
“…Prone positioning has demonstrated improvement in hypoxia at the expense of increasing ICP and decreasing CPP (6,114). Tracheal gas insufflation may allow low tidal volumes with concomitant treatment of hypercarbia or maintenance of normocarbia (87,119). Extracorporeal membrane oxygenation has been used with success in trauma patients with ARDS, particularly demonstrating improved mortality when initiated early (18).…”
Section: Ventilator Management After Tbimentioning
confidence: 99%
“…Several studies have shown that TGI can be used either to decrease PaCO 2 in the setting of hypercapnia or to maintain normocapnia while tidal volume is decreased [66]. In patients with severe head trauma and ALI, Martinez-Perez et al [67] showed that the application of phasic TGI (at mid-to-end expiration) allowed ventilation with lower tidal volumes and driving pressures while maintaining PaCO 2 constant without any deleterious effects on cerebral parameters.…”
Section: Alternative Ventilatory Techniquesmentioning
confidence: 99%
“…Durch transtracheale Katheter konnten wichtige physiologische und klinische Wirkungen des späteren NHF vorweggenommen werden. Dabei konnte eine Reduktion des Totraumes bei zusätzlichem Einsatz eines Flusses durch einen transtrachealen Katheter und eine Reduktion des PCO 2 gezeigt werden [3,4]. Folgeuntersuchungen ergaben, dass das Ausmaß der PCO 2 -Absenkung flowabhängig beeinflusst werden kann [5].…”
Section: Nhf: Pathophysiologische Konzepteunclassified